Building the sugarcane genome for biotechnology and identifying evolutionary trends - Setta, Nathalia de; Monteiro-Vitorello, Claudia Barros; Metcalfe, Cushla Jane; Queiroga Cruz, Guilherme Marcelo; Del Bem, Luiz Eduardo; Vicentini, Renato; Silveira Nogueira, Fabio Tebaldi [UNESP]; Campos, Roberta Alvares; Nunes, Sideny Lima; Gasperazzo Turrini, Paula Cristina; Vieira, Andreia Prata; Ochoa Cruz, Edgar Andres; et al. (Biomed Central Ltd, 2014)
Background: Sugarcane is the source of sugar in all tropical and subtropical countries and is becoming increasingly important for bio-based fuels. However, its large (10 Gb), polyploid, complex genome has hindered genome based breeding efforts. Here we release the largest and most diverse set of sugarcane genome sequences to date, as part of an on-going initiative to provide a sugarcane genomic information resource, with the ultimate goal of producing a gold standard genome.Results: Three hundred and seventeen chiefly euchromatic BACs were sequenced. A reference set of one thousand four hundred manually-annotated protein-coding genes was generated. A small RNA collection and a RNA-seq library were used to explore expression patterns and the sRNA landscape. In the sucrose and starch metabolism pathway, 16 non-redundant enzyme-encoding genes were identified. One of the sucrose pathway genes, sucrose-6-phosphate phosphohydrolase, is duplicated in sugarcane and sorghum, but not in rice and maize. A diversity analysis of the s6pp duplication region revealed haplotype-structured sequence composition. Examination of hom(e)ologous loci indicate both sequence structural and sRNA landscape variation. A synteny analysis shows that the sugarcane genome has expanded relative to the sorghum genome, largely due to the presence of transposable elements and uncharacterized intergenic and intronic sequences.Conclusion: This release of sugarcane genomic sequences will advance our understanding of sugarcane genetics and contribute to the development of molecular tools for breeding purposes and gene discovery.
Keywords: Saccharum; Bacterial artificial chromosome sequencing; Polyploidy; Genome; Genetics; Grasses